2021
DOI: 10.18632/aging.203485
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy alleviates vascular dysfunction and amyloid burden in an Alzheimer’s disease mouse model and in elderly patients

Abstract: Vascular dysfunction is entwined with aging and in the pathogenesis of Alzheimer’s disease (AD) and contributes to reduced cerebral blood flow (CBF) and consequently, hypoxia. Hyperbaric oxygen therapy (HBOT) is in clinical use for a wide range of medical conditions. In the current study, we exposed 5XFAD mice, a well-studied AD model that presents impaired cognitive abilities, to HBOT and then investigated the therapeutical effects using two-photon live animal imaging, behavioral tasks, and biochemical and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 105 publications
1
29
0
Order By: Relevance
“…In these studies, HBOT resulted in an improved learning curve and higher resilience to interference of episodic memory in the healthy young adults [46], and induced cognitive enhancements in healthy aging adults, which were associated with regional improvement in CBF [47]. Similarly, in a recent paper, a group of elderly patients with memory loss at baseline to HBOT showed improved cognitive performances following 60 daily HBOT sessions (2 ATA) and this was associated with an increase in CBF [48]. Interestingly, when HBOT was applied for a short time (only 15 consecutive days), there was no improvement in cognitive impairment in the elderly [49], suggesting that a longer treatment is necessary.…”
Section: Cognitive Improvement In Healthy Individualsmentioning
confidence: 86%
See 2 more Smart Citations
“…In these studies, HBOT resulted in an improved learning curve and higher resilience to interference of episodic memory in the healthy young adults [46], and induced cognitive enhancements in healthy aging adults, which were associated with regional improvement in CBF [47]. Similarly, in a recent paper, a group of elderly patients with memory loss at baseline to HBOT showed improved cognitive performances following 60 daily HBOT sessions (2 ATA) and this was associated with an increase in CBF [48]. Interestingly, when HBOT was applied for a short time (only 15 consecutive days), there was no improvement in cognitive impairment in the elderly [49], suggesting that a longer treatment is necessary.…”
Section: Cognitive Improvement In Healthy Individualsmentioning
confidence: 86%
“…Indeed, a recent study showed that HBOT improves blood flow in an AD mouse model by mitigating the blood vessel constriction that occurs in these AD mice under the regular course of the disease but without HBOT. This was associated with an improved performance of the AD mice [48]. Moreover, in elderly patients with significant memory loss at baseline, HBOT increased CBF and improved cognitive performance [48].…”
Section: Neurogenesis and Angiogenesismentioning
confidence: 90%
See 1 more Smart Citation
“…In these studies, HBOT was shown to alleviate the levels of ROS damage and increase antioxidant activity [ 53 , 54 , 111 ]. As of today, clinical trials focus on the advantageous effects of HBOT on cognitive decline and quality of life for patients suffering from neurodegenerative diseases and show that HBOT improve cognitive functions and ameliorate the reduced brain metabolism in MCI and AD patients [ 10 , 11 , 112 , 113 , 114 ] and in animal models [ 12 , 53 , 111 , 115 , 116 , 117 ]. To better understand the effects of oxidative stress and antioxidant scavenger activity in clinical trials, more research is needed.…”
Section: Disease and Oxidative Stressmentioning
confidence: 99%
“…This 20-fold increase in dissolved oxygen in the blood reaches all body tissues, providing excess oxygen to tissues that are suffering from a lack of delivered oxygen. Hence, HBOT has been used to treat many diseases [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ] and was shown to improve cognition in several brain disorders [ 10 , 11 , 12 , 13 , 14 ]. Although oxygen is needed for energy production in the form of adenine triphosphate (ATP), it can sometimes have deleterious effects when it interacts with other molecules, exchanges electrons and is transformed into reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%